ANALISIS PENGAWASAN DANA DESA DI DESA KUTA KECAMATAN LAMBITU KABUPATEN BIMA PROVINSI NUSA TENGGARA BARAT - Faiqo, Muslimatul; Razak, Rosdianti; Muhiddin, Amir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThe purpose of the study was to determine the form of supervision and effectiveness of village fund supervision. This type of research is descriptive qualitative by explaining the situations or events in a systematic, factual and accurate manner regarding the supervision of village funds in Kuta Village, Lambitu District, Bima Regency, West Nusa Tenggara Province. Data was collected by observation, interviews and documentation. The results of this study indicate that the supervision of the Village Fund is carried out in the form of direct supervision  and indirect supervision  of the implementation of the Village Fund Budget, as well as the obstacles that hinder the BPD in carrying out its supervisory function, including in the form of incompetent human resources and institutionally BPD does not yet have an office. itself, causing less active BPD members in conducting supervision so that the implementation of supervision is not effective enough. Keywords: Supervision, Village Fund, Effective